Role of β(FeAl) nanoparticles in abnormal grain growth in the annealing of cast Cu-Al-Mn-Fe shape memory alloys - Yang, Shuiyuan; Qing, Xinyu; Zhang, Jixun; Guo, Lipeng; Hong, Shen; Li, Mingpei; Zhang, Jinbin; Wang, Cuiping; Liu, Xingjun (Progress in natural science, 2020)
In this study, the low-cost production of Cu-Al-Mn-Fe shape memory alloy single crystals exceeding 46 mm by abnormal grain growth was realized only through annealing their cast alloys. The results show that the misorientation formed during annealing may be responsible for such abnormal grain growth process. It was confirmed that this misorientation resulted from the dissolution of bcc β(FeAl) nanoparticles during heat treatment at a sufficiently temperature of approximately 1173 K. The rate of migration of the abnormal grain boundary was experimentally measured to be approximately 9.3 × 10-5 m s-1 within 2 min of the commencement of abnormal grain growth. Additionally, the range of composition of the alloys that can lead to abnormal grain growth was determined. When the Cu-13.0Al-6.5Mn-3.2Fe single crystal close to the [100] direction was deformed to a pre-strain of 12%, full shape recovery happened without any residual strain. At that time, the superelastic strain was approximately 9%. Such a superelastic characteristic remained nearly constant over 50 cycles, showing excellent fatigue resistance. The superelastic properties of the present Cu-13.0Al-6.5Mn-3.2Fe single crystal are compared to those of commercial Ni-Ti-based shape memory alloys. Therefore, it can be considered as a new kind of superelastic material having practical applications. The obtained results should be of great significance in the development of Cu-based shape memory alloys. Furthermore, it is expected that a similar microstructure can be designed for the production of more metallic single crystals. [Display omitted] •Abnormal grain growth happens when annealing Cu-Al-Mn-Fe cast alloys.•Large shape memory single crystal up to 46 mm in length is obtained.•The dissolution of bcc β(FeAl) nanoparticles results in the misorientation.•Single crystal exhibits excellent superelasticity of 12% and fatigue resistance.